2022
DOI: 10.21037/jgo-22-93
|View full text |Cite
|
Sign up to set email alerts
|

Serum N-glycan profiling as a diagnostic biomarker for the identification of hepatitis B virus-associated hepatocellular carcinoma

Abstract: Background: Changes in N-glycosylation of proteins are thought to play a key role in cancer. This study aims to investigate the changes in the serum N-glycan profiles of patients with hepatitis B virus (HBV)-related liver disease, and to evaluate the role of N-glycan markers in the noninvasive diagnosis of hepatocellular carcinoma (HCC).Methods: Serum samples were available for 21 patients with HCC, 20 patients with liver cirrhosis (LC), 20 patients with chronic hepatitis B (CHB), and 20 healthy subjects. Seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Two studies compared the logarithm of the ratio NA3Fb to NA2FB, AFP, and their combination in diagnosing HCC in HBV‐related cirrhosis. They concluded that the combination of log(NA3Fb/NA2FB) and AFP provided the most accurate diagnostic test performances with AUC values of 0.89 and 0.92 23,24 . Similarly, the logarithm of the ratio of NA3Fb to NG1A2F (single agalacto core‐α‐1,6‐fucosylated bi‐antennary glycan) was able to discriminate between HBV‐infected patients with liver fibrosis and HCC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two studies compared the logarithm of the ratio NA3Fb to NA2FB, AFP, and their combination in diagnosing HCC in HBV‐related cirrhosis. They concluded that the combination of log(NA3Fb/NA2FB) and AFP provided the most accurate diagnostic test performances with AUC values of 0.89 and 0.92 23,24 . Similarly, the logarithm of the ratio of NA3Fb to NG1A2F (single agalacto core‐α‐1,6‐fucosylated bi‐antennary glycan) was able to discriminate between HBV‐infected patients with liver fibrosis and HCC.…”
Section: Resultsmentioning
confidence: 99%
“…Since GnT‐V is competing with N‐acetylglucosaminyltransferase III (GnT‐III) for its substrate, the abundance of bisecting GlcNAc structures, as a product of GnT‐III activity, is downregulated in HCC. Whereas GnT‐V is recognised as pro‐oncogenic glycosyltransferase in several cancer types, GnT‐III mostly presents as tumour suppressor glycosyltransferase 22,23,79,80 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 The liver synthesizes most of the glycosylated serum proteins, and studies have indicated that changes in serum glycopatterns can serve as indicators of liver damage. 9,10 For instance, abnormalities in fucosylation, mannosylation, and sialylation have been observed in cases of liver fibrosis, cirrhosis, and hepatocellular carcinoma. 11−13 While changes in serum glycopatterns have been extensively documented in various liver diseases, there is a lack of systematic studies on the glycopatterns of serum in NAFLD patients.…”
Section: ■ Introductionmentioning
confidence: 99%